Identifikasi Mikroba pada Karkas Ayam Potong Berasal dari RPA Tradisional di Kota Pelaihari - Herliani Herliani (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2015)
The research objectives to microbial identification in broiler carcasses sourced fromtraditional chicken slaughterhouse in Pelaihari. Samples were taken from four traditionalchicken slaughterhouses in Pelaihari. Laboratory test result indicated that 45% samplesshowed total microbial analysis was 1.0x106 - 8.0x107cfu/g. Microbial identification tocarcass contaminated consist of Bacillus sp and Micrococcus sp.